Optimization of Tissue Culturing and Genetic Transformation Protocol for Casuarina equisetifolia - Ren, Huimin; Xu, Yan; Zhao, Xiaohong; Zhang, Yan; Hussain, Jamshaid; Cui, Fuqiang; Qi, Guoning; Liu, Shenkui (Frontiers in Plant Science, 2022)
Casuarina equisetifolia (C. equisetifolia) is widely used in agroforestry plantations for soil stabilization, ecosystem rehabilitation, reclamation and coastal protection. Moreover, C. equisetifolia has remarkable resistance to typhoons, desert, low soil fertility, drought, and salinity, but not cold. Therefore, it is significant to breed high-quality Casuarina varieties to improve the tolerance and adaptability to cold weather by molecular techniques. The establishment of a rapid and efficient callus induction and regeneration system via tissue culture is prerequisite t for the genetic transformation of C. equisetifolia which is so far lacking. In this study, we reported an efficient and rapid regeneration system using stem segment explants, in which callus induction was found to be optimal on the basal medium supplemented with 0.1 mg·L-1 TDZ and 0.1 mg·L-1 NAA, and proliferation on the basal medium containing 0.1 mg·L-1 TDZ and 0.5 mg·L-1 6-BA. For bud regeneration and rooting, the preferred plant growth regulator on basal medium was 0.5 mg·L-1 6-BA, and the combination of 0.02 mg·L-1 IBA and 0.4 mg·L-1 IAA, respectively. We also optimized genetic transformation protocal by using Agrobacterium tumefaciens harboring the binary vector pCAMBIA1301 with β-glucuronidase (GUS) as a reporter gene. Consequently, 5 mg L-1 hygromycin, 20 mg L-1 acetosyringone and 2 days of co-cultivation duration were optimized to improve the transformation efficiency. With these optimized parameters, the transgenic plants were obtained in about 4 months. Besides that, Agrobacterium rhizogenes-mediated transformation involving adventitious root induction was also optimized. Our findings will not only increase the transformation efficiency but also shorten the time for developing transgenic C. equisetifolia plants. Taken together, this pioneer study on tissue culturing and genetic transformation of C. equisetifolia will pave the way for further genetic manipulation and functional genomics of C. equisetifolia.